The politics of Che Guevara : theory and practice - Farber, Samuel (Haymarket Books, 2016)
"Fifty years after his death, Guevara remains a symbol to legions of young rebels and revolutionaries. This book provides a way to critically engage with Guevara's economic views, his ideas about revolutionary agency, and his conduct as guerrilla commander and government administrator in Cuba."--From publisher desciption.